Vingt-cinq ans d’études stratégiques – Essai critique et survol de la documentation - Legault, Albert (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
This article attempts to identify the great issues which have formed the mainstay of the strategic literature over the past twenty-five years. Its is essentially designee to acquaint the student with the major works and debates which have been published or discussed over the same period of time. The only new debates seem to bear on the ecological consequences of a nuclear war, and on the resurgence of the pacifist movements. The last section deals with the major issues of the future, such as outer space, ballistic missile defense, and the potential increase of the risks of a conventional war due to the progress of technology.